Galileo’s Telescope in John Milton’s Paradise Lost: the Modern Origin of the Critique of Science as Instrumental Rationality? - Clemens, Justin (Filozofski vestnik, 2013)
“Almost in the same historical moment when Galileo directed all modern physics to the reading of that book which Nature was supposed to have written herself in geometric or, subsequently, algebraic signs, the modern novel and modern theatre stepped in as evidence that modern readers and spectators enjoy the effects of those fictions most of all when they are altogether free of science.” Friedrich Kittler, “Man as a drunken town musician”